HOW WELL DO THE GENERAL PUBLIC UNDERSTAND PALLIATIVE CARE? A MIXED METHODS STUDY. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - McIlfatrick, Sonja; Hasson, Felicity; Noble, Helen; McLaughlin, Dorry; Roulston, Audrey; Rutherford, Lesley; Johnston, Gail; Kernohan, George
Abstract : Background: International research suggests that the general public appear to be confused about what palliative care is and who provides it. 1 2 An understanding of public views is needed in order to target education and policy campaigns and to manage future needs, expectations and resourcing of care. Aim: The aim of this study was to establish the current levels of awareness and perceptions of palliative care among the general public in Northern Ireland. Methods: A mixed methods study comprising two phases was undertaken. A community-based cross-sectional survey with a population of 3, 557 individuals aged over 17 years was performed. Information was collected using a structured questionnaire consisting of 17 items. Open questions were subject to content analysis; closed questions were subject to descriptive statistics with inferential testing as appropriate. This was followed by semi structured telephone interviews (n=50). Results: Responses indicated limited knowledge about palliative care. Respondents who worked in healthcare themselves or who had a close relative or friend who had used a palliative care service were more aware of palliative care and the availability of different palliative care services. The main barriers to raising awareness were fear, lack of interaction with health services and perception of lack of resources. A key aspect identified for promoting palliative care was the development of understanding and use of the term itself and targeted educational strategies. Conclusions: Public awareness of the concept of palliative care and of service availability remains insufficient. An increased awareness of palliative care is needed, in order to improve knowledge of and access to services when required, empower individuals, involve communities and ultimately to improve the delivery of palliative and end-of-life care. (274)